Kurva Pertumbuhan Sapi Friesian Holstein dari Lahir Sampai Siap Kawin Berdasarkan Tingkat Kelahiran (HOLSTEIN GROWTH CURVE OF NEW BORN CALF UNTIL FIRST MATING BASED ON BIRTH RATE) - Salman, Lia Budimulyati; Sumantri, Cece; Noor, Ronny Rachman; Saefuddin, Asep; Talib, Chalid (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
The growth curve is a reflection of the ability of an individual or population to actualize themselves aswell as the size will be the development of the parts of the body until it reaches the maximum size (adult)on the existing environmental conditions. The main goal of this study is to determine the growth curvemodel of Friesian Holstein cattle from birth until ready to mate based on birth rates with Logistic model,Gompertz, and von Bertalanffy. The data was used in this study is the result of the weighing of dairy cowsbody weight of female Friesian Holstein as many as 335 head number collected by PT Taurus Dairy FarmSukabumi from 2001to 2011, which have complete data from birth until first mating with a birth rate thatis different from the birth of the one to five. The data used in the analysis of growth curves using three nonlineargrowth curve model i.e. Logistic models, Gompertz, and Von Bertalanffy. The results obtainedindicate that the growth curve model shave different levels of accuracy, depending on the environment andage or duration of observation, the longer observed to mature weight (A), the age of puberty, and pubertygreater weight. The Conclusion of this study is a model of Logistic close to field conditions. Morover thehigher the birth rate will be heavier birth weight and adult weight. These three non-linear mathematicalmodel used in this study has a high degree of accuracy.
Keywords: growth curve, birth rate, Friesian Holstein